From temperature to VPD: shifting drivers of flash droughts amplify ecosystem risks in high-latitude cold climates - Long Qi; Chunyu Dong; Tingting Chen; Kairong Lin; Lei Chen; Xiaohong Chen (Journal of Hydrology, 2026)

Seasonal variability and atmospheric drivers of particle-phase PFAS in PM2.5 near a municipal solid waste incineration facility in Nanchang, China - Xiaolu Liu; Dandan Huang; Zehui Zhang; Li Zhang; Xuan Lin; Chunyu Yan; Meng Chen; Renting Nie; Bai Gao; Wenjie Ma; Yuanyuan Liu; Haiyang Zhang (Environmental Pollution, 2026)

Uncovering strain-induced mechanistic divergence of the oxygen evolution reaction on RuO2 - Guokang Han; Yuqi Yan; Dongyue Xin; Zhe Li; Xiaodan Wen; Jiannan Du; Lin Geng; Chunyu Du (Chemical Engineering Journal, 2026)

Soil nutrient effect on microbial diversity and community composition is modulated by soil aggregate fractions in Yuanjiang savanna, China - Jinxiu Zhang; Zihao Guo; Can Wang; Na Lin; Chunyu Hou; Yajun Chen; Meiyan Zhang; Jianping Wu (Applied Soil Ecology, 2026)

Photo-crosslinkable quaternized chitosan-based hydrogel for immunomodulation and functional recovery in spinal cord injury - Kaixuan Chen; Min Lin; Danni Zhou; Kailei Xu; Jin Mei; Chunyu Chang; Mengxiang Zhu; Chenhui Zhou (Carbohydrate Polymers, 2026)

Ecological water replenishment enhances nitrogen removal potential in coastal wetlands by mediating root exudate composition and sediment chemistry - Chunyu Zhao; Songlin Liu; Junliang Wang; Naiqin Zhang; Jingqi Lin; Nana Liu; Kai Di; Donghan Zhang; Changwen Ma; Yang Liu (Marine Pollution Bulletin, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

A tuning-free POD-FV-ROM with automatic boundary enforcement for practical thermal-hydraulic applications - Yang Di; Zhang Chunyu; Lin Jiming; Ding Peng (Annals of Nuclear Energy, 2026)

An Empirical Test of Scale‐Dependence of β‐Diversity in a Large Temperate Forest Region - Liqi Lu; Philip S. Barton; Senxuan Lin; Minhui Hao; Chunyu Fan; Klaus von Gadow; Xiuhai Zhao; Chunyu Zhang (Journal of Biogeography, 2026)
Aim Variation in species composition among locations (β‐diversity) is of fundamental interest in ecology, yet its dependence on spatial extent and grain has rarely been assessed empirically. This study provides a systematic empirical test of the spatial scaling of β‐diversity and highlights the importance of study design for detecting the role of environmental filtering in shaping regional β‐diversity. Location Northeastern China. Taxon Tree in forest ecosystems. Methods We constructed regional communities to define six gradients of spatial extent and grain. We investigated how two types of spatial scale affect a range of aggregate measures of β‐diversity and corresponding β ‐deviations, as well as the distance‐decay relationship (DDR). Variation in β ‐deviations was further partitioned into habitat heterogeneity, spatial aggregation and their joint effects across scales. Results Raw β‐diversity did not exhibit consistent trends with extent across metrics, but it consistently decreased with increasing grain. Both raw β‐diversity and β ‐deviations were strongly influenced by sampling effort. The decreasing trend in Sørensen differentiation ( q = 0) with increasing extent, predicted by theory, was removed after controlling for sampling effort. Notably, only abundance‐based measures showed a significant increase with spatial extent that was unaffected by sampling effort. Sørensen differentiation also decreased with increasing grain, contrary to theoretical expectations. The DDR was sensitive to grain size, and the proportion of variation in β ‐deviations explained by habitat heterogeneity increased with both spatial extent and grain. Main Conclusion The response of raw β‐diversity to extent depended on the metric used and was sensitive to sampling effort. Pairwise abundance‐based measures may provide a more reliable basis for cross‐scale comparisons. The DDR may only be able to capture scale‐specific ecological processes. Environmental filtering emerges as the dominant driver of community assembly at larger spatial scales, highlighting how analytical choices influence inference about assembly mechanisms.

Interface engineering of nanocellulose/PEDOT toward high-strength conductive/thermoelectric fibers - Yujie Pen; Meng Zhou; Jiehan Lin; Na Peng; Mingjie Wu; Chunyu Chang (Chemical Engineering Journal, 2026)

Influence of Sea Surface Temperature on Precipitation Anomalies in Northeast China During the Late Summer, 2024: A Statistical Assessment Based on Generalised Equilibrium Feedback Analysis - Yitong Lin; Yihe Fang; Chunyu Zhao; Yu Zhang; Chang Liu; Xinze Li (International Journal of Climatology, 2026)
During the late summer (July–August) of 2024, the Northeast China (NEC) suffered extreme precipitation and severe floods, with rainfall in southern NEC marking the highest recorded since 1985. Using the daily precipitation records from 245 national meteorological stations across the NEC, this study analyses the characteristics of the rainfall anomalies and the associated large‐scale circulation patterns in the late summer of 2024. Based on the generalised equilibrium feedback analysis (GEFA) method, we investigate the response of precipitation and atmospheric circulation anomalies to sea surface temperature (SST) anomalies across various oceanic basins. The results indicate that the NEC precipitation anomalies in the late summer of 2024 exhibit a remarkable response to both the first empirical orthogonal function (EOF) mode of the North Pacific SST (NP1) and the second EOF mode of the tropical Atlantic SST (TA2). The NP1 features widespread positive SST anomalies extending from the Kuroshio Extension to the west coast of North America, and the TA2 is marked by positive anomalies in the northern tropical Atlantic and negative anomalies in the southeastern region. Both modes induce enhanced precipitation over NEC, with anomaly centres located southward, closely matching the observations. Specifically, the positive SST anomalies of the NP1 mode enhance the upward heat flux over the Japan Sea and its eastern regions, inducing positive geopotential height anomalies over Japan, thereby leading to an enhanced and northward anticyclone in the Northwest Pacific. Moreover, for the TA2 mode, the positive SST anomalies in the northern tropical Atlantic are closely associated with the downstream propagating Rossby wave train, resulting in an anomalous circulation pattern characterised by active Northeast China cold vortexes over the NEC and an intensified western Pacific subtropical high. These circulation anomalies facilitate the northward transport of warm and humid airflows to the NEC and promote the frequent convergence of cold and warm airflows over the NEC region, thereby contributing to the anomalously more precipitation over the NEC in the late summer of 2024. By quantifying the relative contributions of different SST modes, this study helps better target key precursors of NEC summer rainfall anomalies, which provides useful guidance for seasonal climate forecasting in NEC.

Bisphenol AP promotes pulmonary fibrosis by regulating macrophage function in a bleomycin-induced mouse model - Ze Chen; Zhenying Lin; Meng Ni; Baihe Li; Qianqian Zhang; Zelin Cao; Wei Li; Yanan Tang; Dongting Yao; Chunyu Cheng; Yi Hu; Xiaorui Liu; et al. (Toxicology, 2026)

A synthetic biocontrol consortium of Streptomyces salinarius and Bacillus halotolerans exhibits superior protection against Fusarium oxysporum infection in Pinus via synergistic interactions - Haixia Wang; Lin Fu; Chunli Li; Xuanyi Meng; Siyang Wang; Xinlu Zhang; Xinyu Zhou; Xiangna Wang; Fangliang Zheng; Chunyu Zhu (Plant and Soil, 2026)

Control of phosphorus release from sediment by multiple applications of lanthanum-modified palygorskite in the presence of suspended particulate matter input - Chunyu Tian; Jianwei Lin; Yanhui Zhan (Applied Clay Science, 2026)

Designing effective financial pathways for ocean economy: a tripartite evolutionary game perspective - Zhuo Chen; Su Wang; Chunyu Lin (Frontiers in Marine Science, 2026)
The development of the ocean economy plays a vital role in national strategic planning, yet it faces persistent financing challenges due to high risks, long investment cycles, and significant information asymmetries. This study constructs a tripartite evolutionary game model involving government, banks, and marine enterprises to explore effective financial support strategies for the ocean economy. Through replicator dynamic equations, simulation analysis, and sensitivity testing, the study examines how different policy incentives, industry characteristics, and stakeholder behaviors shape stable cooperation outcomes. The findings reveal that the optimal strategy is characterized by government intervention, enterprise investment, and bank exclusive marine financial products establishment, which depends on the alignment of risk compensation, financial incentives, and expected returns. A comparative analysis across three marine sectors—shipping, desalination, and marine equipment—demonstrates that financial support pathways must be tailored to industry-specific risk-return profiles. Policy recommendations include phased subsidies, differentiated incentive mechanisms, and adaptive financial product designs are given. This study provides theoretical support and implementation pathways for marine finance to deliver targeted support for the development of the marine economy.

Exploring the future of sustainable ocean economies: Marine Trade's role in advancing inclusive green growth - Chunyu Lin; Guilin Dai; Ying Liu; Guanqiong Ye; Xiumei Fu (Ocean & Coastal Management, 2026)

The formation of autophagosomes in the development process of rice endosperm is affected by endogenous ascorbic acid - Le Yu; Mengwei Chen; Haoran Yan; Zeliang Ouyang; Xinyu Liu; Sitong Lin; Yixuan Tang; Zhipeng Xu; Chunyu Liu; Peiyi Chen; Liping Zhou; Yonghai Liu (Acta Physiologiae Plantarum, 2026)

Application of nanomaterials in central nervous system disorders - Yixuan Deng; Yani Feng; Bangming Ye; Lei Hu; Lixin Qi; Chenyi Wang; Chunting Zhou; Guanhao Liu; Xiuying Gao; Congying Lin; Qiang Ding; Ziming Zhao; et al. (Psychopharmacology, 2025)

Effects of Nitrogen Deposition, Biodiversity and Climate on Productivity in a Large Temperate Forest Region - Jie Li; Senxuan Lin; Minhui Hao; Chunyu Fan; Juan Wang; Klaus von Gadow; Chunyu Zhang; Xiuhai Zhao (Global Ecology and Biogeography, 2025)
Aim Nitrogen deposition is a widespread global change driver that significantly affects terrestrial ecosystems. However, evidence on the specific mechanisms of productivity response to nitrogen deposition in temperate forests across ecological and climatic gradients is scarce. This study evaluates the effects of nitrogen deposition, multiple attributes of biodiversity and climate on productivity in a large temperate forest region. Location North‐eastern China. Time Period 2017. Major Taxa Studied Woody plants. Methods We assessed taxonomic, functional, and phylogenetic attributes of tree diversity and functional identity of forest communities across a wide range of ecological and climatic conditions. Using partial linear mixed models (LMMs), multivariate LMMs, and structural equation modelling, we investigated the effects and pathways of nitrogen deposition, biodiversity, and climate conditions on productivity. We also explored the relationship between nitrogen deposition and productivity across biotic and climatic gradients. Results Our results show that nitrogen deposition, phylogenetic diversity (PD), and the community‐weighted mean of maximum tree height (CWMHM) are significant positive drivers of productivity. Climate conditions primarily affected productivity indirectly through PD. In species‐poor high‐latitude forests characterised by cold and dry climates, nitrogen deposition had strong positive effects on productivity. That effect weakened towards warmer climatic conditions. Main Conclusions The findings of this study suggest that the response of productivity to nitrogen deposition depends on local ecological and climatic conditions. Our results underscore the importance of considering interactions among multiple global change drivers to improve the accuracy of ecosystem response predictions.

New relationship and mechanisms between Northeast China Cold Vortex and pre-flood season precipitation in South China under global warming - Baihui Guo; Yihe Fang; Yitong Lin; Yiqiu Yu; Chunyu Zhao; Yu Zhang; Yamin Hu; Mingsheng Wang (Climate Dynamics, 2025)

How to promote green transformation of mariculture industry under the influence of financial constraints? A policy simulation based on peer incentive perspective - An Yan; Ying Liu; Chunyu Lin; Wenwen Gu; Qiaorong Yin; Xiumei Fu (Marine Pollution Bulletin, 2025)

Long-term gap regeneration processes in a primary temperate forest of Northeast China: Evidence from integrated multi-temporal remote sensing and field surveys - Danni Wu; Deliang Lu; Chunyu Zhu; Xiaowen Ge; Litao Lin; Tian Gao; Jiaojun Zhu (Forest Ecology and Management, 2025)

Grass-legume polyculture enhances plant productivity and nutrient availability by modulating soil enzymatic activities and microbial communities in grassland - Jawad Ali Shah; Chunyu Yue; Yi Xiong; Na Lin; Jianping Wu (Journal of Soils and Sediments, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Long-term organic farming may prevent nitrate leaching by enhancing the abundance and co-occurrence of nasA-type nitrate assimilatory bacteria - Hui Han; Juan Du; Hanye Ju; Chunyu Wang; Yajuan Fu; Shuanghu Fan; Lin Wang; Xiaoqiang Hou; Qiuzhen Wang (Applied Soil Ecology, 2025)

Comparing Cr(III) oxidation intermediated by different manganese oxidizing bacteria: Efficiencies, kinetic and key structure characteristics of biogenic manganese oxides - Guangyuan Tu; Chunyu Ou; Qi Liao; Xiaoming Zhang; Shuangle Hou; Lin Yu; Kun Li; Sen Yang; Qi Li; Weichun Yang; Qingzhu Li; Mengying Si; et al. (Environmental Research, 2025)

Comprehensive Genome-Wide Analysis and Expression Profiling of the HVA22 Gene Family Unveils Their Potential Roles in Soybean Responses to Abiotic Stresses - Qiumin Chen; Liyue Huang; Xinxia Li; Yuan Ma; Zhenghao Wang; Chunyu Zhang; Feng Lin; Chen Liu (Journal of Plant Growth Regulation, 2025)

Numerical study of relationships between flows and structural characteristics of the rotor in a rim-driven hubless thruster using a strongly-coupling FSI algorithm - Chun Yang; Hua-Dong Yao; Cong Sun; Chao Wang; Chunyu Guo; Jianfeng Lin (Ocean Engineering, 2025)

Mutation Screening of ATXN1, ATXN2, and ATXN3 in Amyotrophic Lateral Sclerosis - Tianmi Yang; Qianqian Wei; Dejiang Pang; Yangfan Cheng; Jingxuan Huang; Junyu Lin; Yi Xiao; Qirui Jiang; Shichan Wang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2025)

Motor-Cognitive Dual-Task Cost and Associated Micro Lesions of Cerebellum and Brainstem in Multiple System Atrophy (Parkinsonian Type) - Yi Xiao; Shichan Wang; Yanbing Hou; Junyu Lin; Tianmi Yang; Qirui Jiang; Jiyong Liu; Ruwei Ou; Chunyu Li; Huifang Shang (The Cerebellum, 2025)

MnOOH/carbon-based reactive electrochemical membrane for aqueous organic pollutants decontamination - Zonglin Pan; Chunyu Wang; Xinyu Liu; Ruisong Xu; Hong Xin; Hang Yu; Lin Li; Shuaifei Zhao; Chengwen Song; Tonghua Wang (Journal of Environmental Management, 2025)

Estimating the impact of 2D urban landscape patterns on extreme precipitation based on non-stationary models in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Xue Xie; Kairong Lin; Mingzhong Xiao; Tian Lan; Chunyu Dong; Jingwen Zhang; Zhaolin Fang (Science of The Total Environment, 2025)

Factors of microbial degradation of organic pollutants: Two meta-analyses - Shibin Liu; Li Guo; Chunyu Xiang; Bowei Zhu; Wenbin Huang; Lin Tian; Jiancheng Tang; Zhanpeng Dai; Ekaterina Filimonenko; Ramzi Mekhalif; Hanzhong Jia; Yakov Kuzyakov (Journal of Cleaner Production, 2025)

Windfarm construction alters soil multinutrient cycling by destabilizing microfauna community in a mountain ecosystem - Debao Li; Changwei Ma; Chunyu Yue; Na Lin; Yingmo Zhu; Jianping Wu (Journal of Environmental Management, 2025)

Pesticide avermectin B1a exerts cytotoxicity by blocking the interaction between mini-chromosome maintenance 6 protein (MCM6) and chromatin licensing and DNA replication factor 1 (CDT1) - Hao Yin; Yaoyao Zheng; Menghan Chen; Ming Ding; Lin Zhang; Roujia Wang; Chunyu Wang; Jing Jia; Xiaoqian Liu (Environmental Pollution, 2025)

The dynamic adjusted system of sea use fees: An empirical research on the sea use management in Zhejiang province - Guanqiong Ye; Zeben Lian; Chong Chen; Chunyu Lin; Zhiguo He; Weidong Shang; Yongchao Zheng (Regional Studies in Marine Science, 2024)

Biodiversity and anthropogenic disturbances predominantly drive carbon sequestration rates across temporal scales in temperate forests - Zhuoxiu Han; Xuetao Qiao; Senxuan Lin; Juan Wang; Chunyu Zhang; Klaus von Gadow (Journal of Environmental Management, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

Molecular mechanism of apoptosis induced by 4-tBP in common carp (Cyprinus carpio L.) head kidneys was explored from various angles: Hippo pathway, miR-203a, oxidative stress, ER stress, and mitochondrial pathway - Jiatian Liang; Xu Lin; Chunyu Jiang; Yuhao Liu; Zhiyu Hao; Minna Qiu; Xiumei Liu; Dechun Chen; Xiaohua Teng; You Tang (Aquaculture, 2024)

Emerging global reservoirs in the new millennium: Abundance, hotspots, and total water storage - Chenyu Fan; Chunqiao Song; Jida Wang; Yongwei Sheng; Yaling Lin; Chunyu Yuan; Md Safat Sikder; Jean-François Crétaux; Kai Liu; Tan Chen; Fanxuan Zeng; Linghong Ke (Science Bulletin, 2024)

Monitoring saltwater intrusion to estuaries based on UAV and satellite imagery with machine learning models - Dingshen Jiang; Chunyu Dong; Zhimin Ma; Xianwei Wang; Kairong Lin; Fang Yang; Xiaohong Chen (Remote Sensing of Environment, 2024)

A novel chain-like conjugated donor-π-acceptor molecular additive for highly efficient and stable perovskite solar cells - Haipeng Jiang; Chunyu Wei; Jin Wang; He Dong; Xinmin Fu; Le Zhang; Fengyou Wang; Lin Fan; Maobin Wei; Huilian Liu; Lili Yang; Yongsheng Yan (Chemical Engineering Journal, 2024)

Sub-Seasonal Predictability of the Northeast China Cold Vortex in BCC and ECMWF S2S Model Forecasts for 2006–2021 - Yiqiu Yu; Jie Wu; Yihe Fang; Chunyu Zhao; Zongjian Ke; Yitong Lin (Journal of Meteorological Research, 2024)

Water Quality Prediction in Urban Waterways Based on Wavelet Packet Denoising and LSTM - Jiafeng Pang; Wei Luo; Zeyu Yao; Jing Chen; Chunyu Dong; Kairong Lin (Water Resources Management, 2024)

Spatially selective defect management of CsPbI3 films for high-performance carbon-based inorganic perovskite solar cells - Hailiang Wang; Qixian Zhang; Zedong Lin; Huicong Liu; Xiaozhen Wei; Yongfa Song; Chunyu Lv; Weiping Li; Liqun Zhu; Kexiang Wang; Zhenhua Cui; Lan Wang; et al. (Science Bulletin, 2024)

Rare DNAJC7 Variants May Play a Minor Role in Chinese Patients with ALS - Shichan Wang; Xiaoting Zheng; Qianqian Wei; Junyu Lin; Tianmi Yang; Yi Xiao; Qirui Jiang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2024)

Dt1 inhibits SWEET-mediated sucrose transport to regulate photoperiod-dependent seed weight in soybean - Xiaoming Li; Zhonghui Chen; Haiyang Li; Lin Yue; Cuirong Tan; Hongjie Liu; Yilong Hu; Yuhua Yang; Xiani Yao; Lingping Kong; Xiang Huang; Bin Yu; et al. (Molecular Plant, 2024)

Impact of heat on emergency hospital admissions related to kidney diseases in Texas: Uncovering racial disparities - Chunyu Guo; Erjia Ge; Manzhu Yu; Changwei Li; Xiangqian Lao; Shuang Li; Jason Glaser; Yongqun He; Marina Almeida-Silva; Sisi Meng; Wei-Chung Su; Junfeng Zhang; et al. (Science of The Total Environment, 2024)

Water rather than nitrogen availability predominantly modulates soil microbial beta-diversity and co-occurrence networks in a secondary forest - Jiayin Feng; Huixia Ma; Chunyu Wang; Jingjing Gao; Changchun Zhai; Lin Jiang; Shiqiang Wan (Science of The Total Environment, 2024)

Screening and degradation characteristics of plastic-degrading microorganisms in film-mulched vegetable soil - Zhenyan Lin; Tuo Jin; Xin Xu; Xiao Yin; Dan Zhang; Mengjiao Geng; Chunyu Pang; Gongwen Luo; Lizhi Xiong; Jianwei Peng; Jiangchi Fei (International Biodeterioration & Biodegradation, 2024)

Bavachin combined with epimedin B induce idiosyncratic liver injury under immunological stress conditions - Mengmeng Lin; Yingying Li; Bo Cao; Jing Xu; Yujun Zhang; Guohui Li; Xiaohe Xiao; Chunyu Li (Chemico-Biological Interactions, 2023)

Chiral design of tough spring-shaped hydrogels for smart umbrellas - Mingqi Chen; Guangjie Song; Bin Ren; Lin Cai; Mokarram Hossain; Chunyu Chang (Chemical Engineering Journal, 2023)

Long-lived paleo-uplift controls on Neoproterozoic–Cambrian black shales in the Tarim basin - Lin Wu; Pengfei Wang; Chunyu Zhang; Xingqiang Feng; Zhuliang Qian; Lei Zhou (Marine and Petroleum Geology, 2023)

Boosting the tumor photothermal therapy with hollow CoSnSx-based injectable hydrogel via the sonodynamic and dual-gas therapy - Lu Jia; Yuzhu Wang; Tingting Hu; Chunyu Yang; Huiming Lin; Feng Zhang; Fengyu Qu; Liru Cui; Wei Guo (Chemical Engineering Journal, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Drought-vulnerable vegetation increases exposure of disadvantaged populations to heatwaves under global warming: A case study from Los Angeles - Chunyu Dong; Yu Yan; Jie Guo; Kairong Lin; Xiaohong Chen; Gregory S. Okin; Thomas W. Gillespie; Jake Dialesandro; Glen M. MacDonald (Sustainable Cities and Society, 2023)

Dynamic changes in permafrost distribution over China and their potential influencing factors under climate warming - Xin Gao; Kairong Lin; Meixian Liu; Chunyu Dong; Zeyu Yao; Zhiyong Liu; Mingzhong Xiao; Xue Xie; Liyan Huang (Science of The Total Environment, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

Experimental study on cotton stalk pyrolysis tar degradation by oxidation in combination with K-containing semi-coke - Fanrui Meng; Qianwang Cheng; Chunyu Fan; Jianting Lin; Yuejun Liu; Xianchun Li (Fuel, 2023)

Impact of heat on all-cause and cause-specific mortality: A multi-city study in Texas - Chunyu Guo; Kevin Lanza; Dongying Li; Yuyu Zhou; Kristin Aunan; Becky P.Y. Loo; Jason Kai Wei Lee; Bin Luo; Xiaoli Duan; Wangjian Zhang; Zhengjun Zhang; Shao Lin; et al. (Environmental Research, 2023)

Cobalt nanoparticles induce mitochondrial damage and β-amyloid toxicity via the generation of reactive oxygen species - Jingrong Chen; Cheng Chen; Na Wang; Chunyu Wang; Zhaohui Gong; Jingxian Du; Honglin Lai; Xinpei Lin; Wei Wang; Xiangyu Chang; Michael Aschner; Zhenkun Guo; et al. (NeuroToxicology, 2023)

Expired yogurt-derived, three-dimensional water evaporator with sustainable self-cleaning and high mechanical properties for the desalination and purification of oil-contaminated seawater - Yahui Liu; Yitong Cui; Chunyu Yang; Huiming Lin; Feng Zhang; Kai Yu; Wei Guo; Fengyu Qu (Desalination, 2023)

An Evaluation of the Coupling Coordination of Technological Innovation System in China’s Marine Biopharmaceutical Industry - Xiumei Fu; Yangming Zheng; Chunyu Lin; Ping Wang; Changyun Wang (Journal of Ocean University of China, 2023)

The Coordinated Influence of Indian Ocean Sea Surface Temperature and Arctic Sea Ice on Anomalous Northeast China Cold Vortex Activities with Different Paths during Late Summer - Yitong Lin; Yihe Fang; Chunyu Zhao; Zhiqiang Gong; Siqi Yang; Yiqiu Yu (Advances in Atmospheric Sciences, 2023)

Two types of cold waves affecting northeast China and the corresponding different key regions of precedent sea ice and sea surface temperature - Yihe Fang; Yitong Lin; Chunyu Zhao; Shiqi Xu; Yi Lin; Yiqiu Yu (International Journal of Climatology, 2022)
Based on the daily minimum temperature data from 199 meteorological stations in northeast China (NEC), the cold wave (CW) processes in winter from 1980 to 2020 are identified. Then, by using the reanalysis 500‐hPa geopotential height data provided by the European Centre for Medium‐Range Weather Forecasts (ECMWF), the CWs are objectively classified into two types (abbreviated as Type 1 and Type 2) according to the corresponding atmospheric circulation through the hierarchical cluster algorithm (HCA). The relationships of the CWs with the Arctic sea sic (SIC) and sea surface temperature (SST) are revealed. For Type 1, the SIC in the north of the Barents Sea–Kara Sea is relatively less in the previous autumn, and a wave train propagating from the polar regions to Northeast Asia is stimulated under the ice–atmosphere interaction. This wave train further cooperates with the positive SST anomaly in the southern Indian Ocean to excite the low‐vortex circulation under the negative phase of Arctic Oscillation (AO) in winter, which is conducive to the occurrence of Type 1. However, the relatively low SST in the western Pacific warm pool in previous autumn stimulates a northward propagating wave train along the meridian, which increases the degree of meridionality of the atmospheric circulation over East Asia and thus indirectly causes the polar‐vortex‐splitting circulation under the positive AO phase, which favours the formation of Type 2. The numerical simulations can well reproduce the observational facts, further confirming the possible impact of the SIC and SST in the previous autumn on the two types of CW over the NEC.

FAM135B: a new player in DNA damage response - Chunyu Song; Lin Deng (Genome Instability & Disease, 2022)

Efficiently immobilizing uranium (VI) by oxidized carbon foam - Hongliang Bao; Chunyu Xie; Ling Han; Zenghui Yue; Yuan Qian; Linjuan Zhang; Zi-Jian Li; Huangjie Lu; Jian Lin; Jian-Qiang Wang (Environmental Science and Pollution Research, 2021)

Classification of Northeast China Cold Vortex Activity Paths in Early Summer Based on K-means Clustering and Their Climate Impact - Yihe Fang; Haishan Chen; Yi Lin; Chunyu Zhao; Yitong Lin; Fang Zhou (Advances in Atmospheric Sciences, 2021)

Neoproterozoic glaciations and rift evolution in the northwest Tarim Craton, China: new constraints from geochronological, geochemical, and geophysical data - Lin Wu; Shuwei Guan; Rong Ren; Chunyu Zhang; Xingqiang Feng (International Geology Review, 2021)

Numerical and Experimental Study of Flow Field between the Main Hull and Demi-Hull of a Trimaran - Cong Sun; Chunyu Guo; Chao Wang; Lianzhou Wang; Jianfeng Lin (Journal of Marine Science and Engineering, 2020)
The interactions between the main hull and demi-hull of trimarans have been arousing increasing attention, and detailed circumferential flow fields greatly influence trimaran research. In this research, the unsteady wake flow field of a trimaran was obtained by Reynolds-Averaged Navier-Stokes (RANS) equations on the basis of the viscous flow principles with consideration of the heaving and pitching of the trimaran. Then, we designed an experimental method based on particle-image velocimetry (PIV) and obtained a detailed flow field between the main hull and demi-hull of the trimaran. A trimaran model with one demi-hull made of polycarbonate material with 90% light transmission rate and a refractive index 1.58 (close to that of water 1.33) was manufactured as the experiment sample. Using polycarbonate material, the laser-sheet light-source transmission and high-speed camera recording problems were effectively rectified. Moreover, a nonstandard calibration was added into the PIV flow field measurement system. Then, we established an inverse three-dimensional (3D) distortion coordinate system and obtained the corresponding coordinates by using optics calculations. Further, the PIV system spatial mapping was corrected, and the real flow field was obtained. The simulation results were highly consistent with the experimental data, which showed the methods established in this study provided a strong reference for obtaining the detailed flow field information between the main hull and demi-hull of trimarans.

Real-Time Prediction of Large-Scale Ship Model Vertical Acceleration Based on Recurrent Neural Network - Yumin Su; Jianfeng Lin; Dagang Zhao; Chunyu Guo; Chao Wang; Hang Guo (Journal of Marine Science and Engineering, 2020)
In marine environments, ships are bound to be disturbed by several external factors, which can cause stochastic fluctuations and strong nonlinearity in the ship motion. Predicting ship motion is pivotal to ensuring ship safety and providing early warning of risks. This report proposes a real-time ship vertical acceleration prediction algorithm based on the long short-term memory (LSTM) and gated recurrent units (GRU) models of a recurrent neural network. The vertical acceleration time history data at the bow, middle, and stern of a large-scale ship model were obtained by performing a self-propulsion test at sea, and the original data were pre-processed by resampling and normalisation via Python. The prediction results revealed that the proposed algorithm could accurately predict the acceleration time history data of the large-scale ship model, and the root mean square error between the predicted and real values was no greater than 0.1. The optimised multivariate time series prediction program could reduce the calculation time by approximately 55% compared to that of a univariate time series prediction program, and the run time of the GRU model was better than that of the LSTM model.

Prediction of Self-Propulsion Performance of Ship Model with Double L-Type Podded Propulsors and Conversion Method for Full-Scale Ship - Dagang Zhao; Chunyu Guo; Jianfeng Lin; Zuotian Zhang; Xue Bai (Journal of Marine Science and Engineering, 2019)
In this study, the self-propulsion performance of a ship model with double-L-type podded propulsors was predicted. Additionally, a conversion method for the performance of a full-scale ship was established based on the correction method published by the International Towing Tank Conference (ITTC) for the scaling effect of a single podded propeller and research reports on pod tests conducted by different ship research institutes. The thrust deduction and wake fraction of the ship were also analyzed. Furthermore, the self-propulsion performance of a full-scale ship with double L-type pods was determined, the full- and model-scale ships compared in terms of their flow fields and pressure charts, and the influence of the scaling effect analyzed. In addition, the calculation results were compared with the conversion results of a full-scale ship, and the reliability of the method adopted for the performance estimation of a full-scale ship with double podded propulsors was verified. The findings reported herein can provide statistics and technical support for the design of L-type podded propulsors and their application in full-scale ships, which are of theoretical significance and practical value in the engineering domain.

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Phylogenetic analysis of STK gene family and Usp domain in maize - Ting Zhou; Mingxia Fan; Muhammad Irfan; He Wang; Dongxu Wang; Lin Wang; Chunyu Zhang; Lin Feng (Molecular Biology Reports, 2014)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

An experimental study on the wave-induced pore water pressure change and relative influencing factors in the silty seabed - Anlong Li; Xiaoqiao Luo; Lin Lin; Qing Ye; Chunyu Le (Journal of Ocean University of China, 2014)

Anatomical adaptations of the xerophilous medicinal plant, Capparis spinosa, to drought conditions - Lu Gan; Chunyu Zhang; Yongtai Yin; Zhiwei Lin; Yongwei Huang; Jun Xiang; Chunhua Fu; Maoteng Li (Horticulture, Environment, and Biotechnology, 2013)

Association of polymorphisms in folate metabolic genes and prostate cancer risk: a case-control study in a Chinese population - Dawei Cai; Lin Ning; Chunyu Pan; Xuefeng Liu; Renge Bu; Xiaonan Chen; Kefeng Wang; Yang Cheng; Bin Wu (Journal of Genetics, 2010)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

St abilization of summer monsoon in middle and lower reaches of the Changjiang river and seasonal transition of East-Asian circulation pattern in early summer - Chunyu Lin (Advances in Atmospheric Sciences, 1985)